PENGARUH TRANSAKSI PIHAK BERELASI DAN ENVIRONMENTAL SOCIAL GOVERNANCE TERHADAP NILAI PERUSAHAAN DI MASA PANDEMI COVID-19 - Eni Susilowati; Noer Sasongko (LP2M Universitas Bina Bangsa, 2024)
This study aims to examine the influence of related party transactions and environmental social governance on company value during the COVID-19 pandemic on manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique used in this study is purposive sampling. A total of 15 companies with a total sample of 54 samples. The analysis method used is multiple linear regression analysis. The results of the study provide empirical evidence that the transactions of related parties affect the value of the company. Meanwhile, environmental social governance has no effect on the company's value